2020
DOI: 10.2147/cia.s222490
|View full text |Cite
|
Sign up to set email alerts
|

<p>Behavioral Conformity of Physical Activity and Sedentary Behavior in Older Couples with One Partner Suffering from End-Stage Osteoarthritis</p>

Abstract: Purpose: The present study investigates behavioral conformity regarding physical activity (PA) and sedentary behavior (SB) in older couples where one partner suffers from osteoarthritis (OA). Hereby the question is addressed whether and to what extent the typical physical limitations of OA patients have negative effects on their partners. Patients and Methods: The habitual PA and SB of end-stage osteoarthritis patients (n = 32, 52-81 years | n = 14 gonarthrosis, n = 18 coxarthrosis), their spouses (n = 32, 50-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 63 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…This study has some limitations. First of all, only a small group, i.e., 16 patients, conveniently taken from a larger cohort [ 23 ], was included in the study. This small number might reduce the odds of detecting true effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study has some limitations. First of all, only a small group, i.e., 16 patients, conveniently taken from a larger cohort [ 23 ], was included in the study. This small number might reduce the odds of detecting true effects.…”
Section: Discussionmentioning
confidence: 99%
“…First, because it has been shown that an increase of sedentary activities in old age is associated with a loss of everyday skills, which cannot be compensated for by PA [ 42 ]. Second, because it was demonstrated that the sedentary lifestyle of OA patients is adopted by their partners [ 23 ], and thus, it could affect a much larger group of people than previously thought. The development of noncommunicable diseases and the possible loss of independence in everyday life due to excessive SB is a great challenge, not only for individuals, but also for the health care systems [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 Consequently, it is likely that the inactive lifestyle of OA patients might be adopted by their partners. Indeed, it has recently been shown that OA patient-partner dyads differ significantly from control couples in terms of PA. 21 With regard to SB, it was even found that both partners and controls were in fact at the same level as the OA patients, which could be attributed to the widespread sedentary lifestyle in today’s society. 22 , 23 …”
Section: Introductionmentioning
confidence: 97%